2010
DOI: 10.1007/s12012-010-9076-9
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate (Punica granatum L.) Juice Supplementation Attenuates Isoproterenol-Induced Cardiac Necrosis in Rats

Abstract: The aim of the present study was to evaluate the efficacy of pre-supplementation with pomegranate (Punica granatum L.) juice (PJ) on heart weight, infarct size, plasma marker enzymes of cardiac damage, lipid peroxidation, endogenous enzymatic and non-enzymatic antioxidants, cardiac ATPases and histopathology of isoproterenol (IP)-induced cardiac necrosis (CN) in rats. Rats treated with IP (85 mg/kg, s.c.) for 2 days at an interval of 24 h caused significant (P < 0.05) infarct in myocardium and increase in hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
(36 reference statements)
6
20
0
Order By: Relevance
“…Level of MDA, a major oxidation product of peroxidized poly unsaturated fatty acids, has been considered to be an important indicator of lipid peroxidation [42]. In the current study, high levels of cardiac MDA in cadmiumexposed rats indicate heightened lipid peroxidation and prevalent oxidative stress as has been reported for cadmium and other heavy metal intoxication [43,44].…”
Section: Discussionsupporting
confidence: 62%
“…Level of MDA, a major oxidation product of peroxidized poly unsaturated fatty acids, has been considered to be an important indicator of lipid peroxidation [42]. In the current study, high levels of cardiac MDA in cadmiumexposed rats indicate heightened lipid peroxidation and prevalent oxidative stress as has been reported for cadmium and other heavy metal intoxication [43,44].…”
Section: Discussionsupporting
confidence: 62%
“…There was a significant (p < 0.05) increase in the level of lipid peroxidation in the heart tissue of Group III isoprenaline-administered rats as compared to controls (Table 3). This concurs with the findings of Jadeja et al [24], which indicated that the higher vulnerability of myocardium to peroxidative damage was mainly due to deterioration in the level of free radical scavengers. Lipid peroxidation of membranes is delimited by the availability of substrate in the form of PUFA, the availability of inducers such as free radicals and excited state molecules to promote propagation, the antioxidant defense status of environment and the physical status of the membrane lipid bilayer [9].…”
Section: Effect Of Dietary Chitosan Supplementation On Body Weight Ansupporting
confidence: 93%
“…An absence of cardiotoxicity following long-term PE consumption as opposed to various synthetic inhibitors of COX-2, evidenced from our noninvasive echocardiographic assessment, represents an important finding of our current study. Several laboratories have reported the protective effects of pomegranate juice or extract against experimentally induced cardiotoxicity in rats [52,53].…”
Section: Discussionmentioning
confidence: 99%